Early Tournaisian ammonoids from Timimoun (Gourara, Algeria) - V. Ebbighausen; J. Bockwinkel; D. Korn; D. Weyer (Fossil Record, 2004)
A small ammonoid fauna, of probable middle Early Tournaisian age, is described from the Gara el Kahla near Timimoun, Gourara, Algerian Sahara. The following taxa are described: Acutimitoceras algeriense n. sp., Acutimitoceras sinulobatum n. sp., Acutimitoceras sp. A, Hasselbachia gourara n. sp., Gattendorfia jacquelinae n. sp., Gattendorfia cf. crassa Schmidt. 1924, Kahlacanites n. gen., Kahlacanites meyendorfi n. sp., Kahlacanites mariae n. sp., and Kahlacanites timimounensis n. sp.Eine kleine Ammonoideenfauna mit wahrscheinlich mittlerem Untertournai-Alter von der Gara el Kahla bei Timimoun (Gourara, Algerische Sahara) wird untersucht. Die folgenden Taxa warden beschrieben: Acutimitoceras algeriense n. sp., Acutimitoceras sinulobatum n. sp., Acutimitoceras sp. A, Hasselbachia gourara n. sp., Gattendorfia jacquelinae n. sp., Gattendorfia cf. crassa Schmidt, 1924, Kahlacanites n. gen., Kahlacanites meyendorffi n. sp., Kahlacanites mariae n. sp. und Kahlacanites timimounensis n. sp.doi:10.1002/mmng.20040070107